Determining the effect of developmental ‘HR nurturing connect’ interventions on compassion and empathy in physicians and surgeons - Solanki, Dhiraj (International Journal of Research in Medical Sciences, 2024)
Background: Empathy in healthcare, particularly therapeutic empathy, is vital for understanding and validating patients’ emotions, leading to better patient care and outcomes. Despite its benefits, empathy often declines during medical training. While various training programs aim to enhance empathy are designed, there is a need for standardized methods and more qualitative research to address this. Therefore, in the current study, to enhance the combined concept of empathy and compassion, developmental interventions called "HR nurturing connects” (HRNC) were implemented. Methods: This two-arm, prospective, randomized study involving 28 doctors. 14 doctors in the intervention group underwent the HRNC training which focused on enhancing empathy and compassion through training modules and constructive feedback. Whereas the control group received no developmental intervention. Evaluation for parameters of empathy and compassion were evaluated by using the cumulative Bhaktivedanta’s index of compassion and empathy in physicians and surgeons (BICEPS) score which involved assessments from doctors and 2 nurses, 2 ward clerks working with respective doctors at multiple time points. Results: The intervention significantly increased empathy and compassion (p<0.001) of the doctors randomized in intervention group, with BICEPS scores rising from 66.51±3.87 (baseline) to 84.12±7.43 (12 months). In contrast, the control group showed minimal changes, with scores increasing from 63.48±4.56 (baseline) to 69.5±4.87 (12 months). Conclusions: The ‘HRNC’ program has proven effective in enhancing empathy, compassion, kindness, and understanding in doctors, resulting in better patient outcomes, an improved workplace environment, and higher overall healthcare quality.